Self-Disclosure of Child Sexual Abuse victim: Interpersonal Communication Perspective - Wijayanti, Tutut Nur Tyas; Rahmanto, Andre N; Sudarmo, Sudarmo (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2018)
This study was aimed at finding out the dimension of interpersonal communication in self-disclosure of Child sexual abuse victim. The research method of the study was qualitative descriptive with phenomenological approach. The data were collected by using an in-depth interview. The interview was conducted with three informants determined through snowball sampling technique where informant A recommended informant B and so forth. The result of the study showed that interpersonal communication dimensions namely openness, empathy, supportiveness, and positiveness are needed by child sexual abuse victim self-disclosure. The finding of the study showed that three child sexual abuse victims need good interpersonal communication to be self-disclosed in accordance with the investigation need. The finding of the study can be used as reference to develop guidance and counseling program for child sexual abuse victims.